2019
DOI: 10.1186/s12883-018-1225-y
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk after transient ischemic attack in a Norwegian prospective cohort

Abstract: BackgroundTransient ischemic attack (TIA) is a risk factor of stroke. Modern treatment regimens and changing risk factors in the population justify new estimates of stroke risk after TIA, and evaluation of the recommended ABCD2 stroke risk score.MethodsFrom October, 2012, to July, 2014, we performed a prospective, multicenter study in Central Norway, enrolling patients with a TIA within the previous 2 weeks. Our aim was to assess stroke risk at 1 week, 3 months and 1 year after TIA, and to determine the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 19 publications
1
31
1
Order By: Relevance
“…In recent decades, several studies conducted in a wide range of different settings have focused on the association between transient ischaemic attack (TIA) and the risk of stroke [3][4][5][6][7][8][9][10][11][12][13][14]. Whilst these results have shed some light on the association between TIA and stroke, they also have had several limitations that must be acknowledged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, several studies conducted in a wide range of different settings have focused on the association between transient ischaemic attack (TIA) and the risk of stroke [3][4][5][6][7][8][9][10][11][12][13][14]. Whilst these results have shed some light on the association between TIA and stroke, they also have had several limitations that must be acknowledged.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, most of the recent studies followed participants for 5 years or less [7][8][9][10]13], so the long-term risk of stroke and associated predictors in patients with a history of TIA remains largely unknown. Thirdly, only one previous study was conducted in Germany [10] and, given that stroke incidence is particularly high in Germany [16], more research investigating risk factors for this neurological condition in this country is needed.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in line with the risks described in our own prospective TIA cohort. 7 Other recent studies reporting the effect of rapid evaluation and treatment initiation of TIA patients have found similar low stroke risks. 3,4,17,18 As described earlier, 7 this trend towards a lower stroke recurrence during the recent years may be explained by more rapid evaluation by stroke specialists, better implementation of secondary stroke prevention strategies, as well as changing risk factors in the population, for instance through a decline in cigarette smoking rates.…”
Section: Discussionmentioning
confidence: 69%
“…6 In our prospective TIA study, MIDNOR TIA, we found a lower stroke risk after TIA than reported in earlier studies. 7 The ABCD2 score was able to identify patients with very low risk of stroke, but did not reliably discriminate between low and high-risk patients, suggesting that it may be less useful in populations with a general low risk of stroke after TIA. The primary aim of the present study was to investigate the predictive accuracy of the ABCD3-I score and secondary to compare it with the ABCD2 score in short-and long-term risk strati cation, and to test whether ABCDI-3 score performed better in populations with a low risk of stroke after TIA.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation